Post-treatment effects of subantimicrobial dose doxycycline on clinical parameters and gingival crevicular fluid transforming growth factor-b1 in severe, generalized chronic periodontitis - A Gu¨rkan (Journal compilation 2008 Blackwell Munksgaard, 2008)
Present study aimed to evaluate the effect of 3-month adjunctive subantimicrobial dose doxycycline (SDD) on clinical parameters and gingival crevicular fluid (GCF) transforming growth factor-beta1 (TGF-b1) levels in chronic periodontitis patients over 12 months.